1993
DOI: 10.1080/00039896.1993.9940814
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tubular Function after Reduction of Environmental Cadmium Exposure: A Ten-year Follow-up

Abstract: A prospective follow-up study was carried out to assess the prognosis of renal tubular function after reduction of environmental cadmium exposure. Time-related changes in urinary beta 2-microglobulin and cadmium excretion were followed from 1979 to 1989 in 102 residents of a cadmium-polluted area in Nagasaki, Japan. The average dietary cadmium intake among the study population was more than 200 micrograms/d in 1969, which decreased to approximately half that amount in 1983 because cadmium-polluted paddy fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 12 publications
3
34
0
1
Order By: Relevance
“…Results of previous investigations have suggested that proteinuria resulting from high cadmium exposures has been irreversible and progressive (13,37), but reversibility of minor renal changes was found among workers following a reduction in cadmium exposure (38). The clinical significance of the observed relationship between low-level urinary cadmium and urinary NAG and AAP is difficult to discern.…”
Section: Discussionmentioning
confidence: 95%
“…Results of previous investigations have suggested that proteinuria resulting from high cadmium exposures has been irreversible and progressive (13,37), but reversibility of minor renal changes was found among workers following a reduction in cadmium exposure (38). The clinical significance of the observed relationship between low-level urinary cadmium and urinary NAG and AAP is difficult to discern.…”
Section: Discussionmentioning
confidence: 95%
“…Kido et al (1988) and Iwata et al (1993) reported that the dysfunction of renal tubules after Cd exposure may become irreversible when β 2 -MG-U cr levels exceed 1,000 μ g / g cr. In a long run, an increase in mortality and reduction in life span was also observed among the residents with 1,000 μ g β 2 -MG / g cr in urine (Iwata et al 1991;Nishijo et al 1994;Arisawa et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The group in Area A in the upper-left corner in the figure included many cases of Itai-itai disease patients and suspects who were all at advanced ages (AM age of cases was in a range of 65 to 82 years with the eldest at 91 years; e.g., Kasuya et al 1992;Aoshima 2004). It is conceivable that while Cd-U cr decreased during hospitalization, tubular dysfunction stayed unimproved or even progressed (Kido et al 1988;Iwata et al 1993), so that Cd-U cr levels were relatively low although β 2 -MG-U cr levels were high. In Area B which is just below Area A, there was no case of the patients or suspects (e.g., Ogata et al 1976;Saito et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Edling et al (1986), reported subjects exposed to 0.5mg Cd/m 3 had induced renal damage in the form of beta 2-microglobunuria [15]. Iwata et al (1993) and Butchet et al (1990) also obtained similar results, these investigators found associations between levels of cadmium exposure with proteinuria and glomerular filtration rate among workers exposed to cadmium oxide in a nickel-cadmium battery manufacturing factory [16,17].…”
Section: Exposure To Cadmium and Potential Adverse Health Effectsmentioning
confidence: 68%